Validation of the Portuguese Version of the Antisocial Process Screening Device–Self-Report With a Focus on Delinquent Behavior and Behavior Problems - Pechorro, Pedro (2013)
The main objectives of the present study were to validate a Portuguese version of the Antisocial Process Screening Device-Self-Report and to evaluate the predictive importance of some constructs in discriminating between inmate delinquent youth and community youth. With a total of 760 participants, male (n = 543) and female (n = 217), divided in an inmate forensic sample (n = 250) and a community sample (n = 510), the authors were able to demonstrate psychometric properties that justify its use with the Portuguese juvenile population, in terms of factor structure, internal consistency, temporal stability, convergent validity, divergent validity, concurrent validity, and cutoff score. The predictive importance of psychopathic traits, self-reported delinquent behavior, and behavior problems on the prediction of sample membership (forensic vs. community) was established by binary logistic regression.